The margins of labour cost adjustment: Survey evidence from European firms - Jan Babecky; Philip Du Caju; Theodora Kosma; Martina Lawless; Julian Messina; Tairi Room (National Bank of Belgium, 2009)
Firms have multiple options at the time of adjusting their wage bills. However, previous literature has mainly focused on base wages. We broaden the analysis beyond downward rigidity in base wages by investigating the use of other margins of labour cost adjustment at the firm level. Using data from a unique survey, we find that firms make frequent use of other, more flexible, components of compensation to adjust the cost of labour. Changes in bonuses and non-pay benefits are some of the potential margins firms use to reduce costs. We also show how the margins of adjustment chosen are affected by firm and worker characteristics
Keywords: J30; C81; P5; 330; labour costs; wage rigidity; firm survey; European Union; Arbeitskosten; Vergütungssystem; EU-Staaten